Land Degradation Neutrality — the modern approach for land management and policy-making - G. S. Kust; O. V. Andreeva; V. А. Lobkovskiy (Проблемы постсоветского пространства)
The land reform affected all the countries of the post-Soviet space and in the number of cases led to land degradation, as indicated in scientific literature and in the state reports. The paper presents the results of applying the modern international methodology for Land Degradation Neutrality (LDN) assessment for the Russian Federation. The tools of this methodology makes it possible to trace, on a retrospective basis, the dynamics of land degradation using following proxy indicators: land cover, land productivity and soil organic carbon stocks. The relevant data for 2000-2015 are provided in the paper. It is shown that, despite the convenience and relative simplicity of the international methodology, as well as the possibility for comparative analysis of the state of land for the entire territory of the country according to a unified methodology, nevertheless it can not be used as alternative methods through direct substitutions of the global LDN indicators to national counterparts. The main reasons for the contradictions revealed are the variety of socio-economic and socio-economic conditions, as well as the existing multi-level state system for land monitoring and assessment, which is traditional and conservative. To harmonizing national and global data it is proposed to enhance the national land monitoring system with global indicators for using them in the national land assessment system to monitor and verify the accuracy of statistical data obtained by traditional methods. In this case, global LDN indicators can be used in state and sectoral statistics to analyze general trends and stimulate the LDN targeting at the national and local level. The method for LDN calculation allows comparing poorly compared land categories by degradation indicators, although it will require substantial refinement for use in the Russian Federation.